Early pottery in Transbaikal Siberia: New data from Krasnaya Gorka. (20th June 2017) - Tsydenova, Natalia; Andreeva, Darima; Zech, Wolfgang
Abstract: The paper presents new results of the site Krasnaya Gorka located in Transbaikal Siberia. New AMS dates from this site now attest to a Late Pleistocene occupation phase with early pottery. The evidence from this site enables the study of the development of pottery types and of lithic technology as two main parts of material culture at the Pleistocene-Holocene transition on the materials of Krasnaya Gorka. On a wider scale, the complex is compared with other sites with early ceramics in Transbaikal. Some biogeochemical proxies like pyrogenic carbon, phosphorus, total organic carbon, potassium, magnesium and the stable isotope 15N were analyzed to get an idea about the intensity of human occupation.